ESTUDIO COMPARADO SOBRE EL PERFIL DE LOS PARTICIPANTES DE EDUCACIÓN SECUNDARIA DE ADULTOS DE CATALUÑA (ESPAÑA) Y DEL DISTRITO FEDERAL (BRASIL) | Comparative study on the profile of the adult secondary education participants in Cataluña (Spain) and in Federal District (Brazil) (Trabalho & Educação, 2018)
This article contemplates reflections about the profile of the participants of high school classes, in the youth and adult education (EJA) modality, of two contexts: Catalonia (Spain) and the Federal District (Brazil). One of the reflexes points to a trend of Young people dropping out of regular secondary education; and who subsequently return to the educational system in EJA programs, which has produced a new public profile and inadequacies in the pedagogical proposal. Therefore, the study is based on a methodology of comparative study, with a double approach (qualitative and quantitative), aiming to know and understand the opinion of the participants about the importance of high school, therefore, records the description of the secondary school organization adults, the methodology used in the study and some research results, such as the need to link the pedagogical proposal to this new public of the EJA, this corroborates to think of a high school offer that represents this new panorama.___Este artigo contempla algumas reflexões em torno do perfil dos participantes de classes de ensino médio, na modalidade educação de jovens e adultos (EJA), de dois contextos: Catalunha (Espanha) e Distrito Federal (Brasil): Estas reflexões são oriundas da tese de doutorado, e faz menção a uma tendência de jovens que abandonam o ensino médio regular; e que posteriormente regressam ao sistema educativo, em programas de EJA, o que tem produzido um novo perfil de público e inadequações da proposta pedagógica. Para tanto, o estudo se apoia numa metodologia de estudo comparado, com dupla abordagem (qualitativa e quantitativa), com o objetivo de conhecer e compreender a opinião dos participantes sobre a importância do ensino médio, portanto, registra a descrição da organização da secundaria de adultos, a metodologia emprega no estudo e alguns resultados da pesquisa, como a necessidade de se atrelar a proposta pedagógica a esse novo público da EJA, com isso corrobora a se pensar em uma oferta de ensino médio que represente esse novo panorama.